STUDENTS’ PERCEPTION OF CULTURAL VALUES IN “TRAVEL” POEM THROUGH YOUTUBE - Danti Pudjiati; Zuriyati Zuriyati (IJLECR (International Journal of Language Education and Cultural Review), 2022)
Since the popularity of YouTube as one of the sources to learn language especially English in digital era, students in tertiary education nowadays tend to appreciate a poem through this platform. The research about appreciating the cultural values of English poem is still far on the ground. Therefore, this study focuses to find out the students perception of cultural values in “Travel” as a classical poem by Robert Stevenson. The qualitative method of interview and online survey is conducted to obtain the students’ views of cultural values proposed by Schwart. The result revealed that they stated stimulation, self-direction, conformity and tradition as the cultures values expressed in that poem. However students selected youTube as the most preference way in appreciating the poem due to its attractive visual and vast imagination.